Aesthetic Values in the Lyrics of the Song ภูเขา (Pūkheā) by Wing Sentot Irawan - Nurtikawati, Nurtikawati (Gema Cendekia Institute, 2025)
Abstract This research examines the aesthetic values embedded in the lyrics of the song ภูเขา (Pūkheā) by Wing Sentot Irawan. Through an aesthetic analysis approach, this paper aims to reveal the visual and auditory dimensions contained within the song. Furthermore, this study seeks to explore the philosophical meanings and reflections on life experiences as depicted by the composer. By investigating the interaction between text, context, and musical elements, this article demonstrates how the lyrics of this song serve not only as a musical composition but also as a medium of communication that possesses aesthetic significance, showcasing the interrelations of various components. The research was conducted using a descriptive qualitative research method with an ethnomusicological approach. The findings indicate that the lyrics of the song ภูเขา (Pūkheā) by Wing Sentot Irawan depict not only a physical journey but also an inner journey that embodies aesthetic values. The lyrics illustrate a harmonious relationship between language, nature, and civilization. By employing elements of nature, culture, and personal journeys as symbols, this song invites listeners to reflect on the meanings of life, civilization, and achievement.